Verb Go (back to, on, and out) in English for TEFL in the Novel of New Moon by Stephenie Meyer: The Syntactic and Semantic Analysis - Helmie, Jauhar (EDUCARE, 2015)
ABSTRACT: Languages use visual symbols to represent the sounds of the spoken languages, but they still require syntactic rules that govern the production of meaning from sequences of words. While, a phrasal verb is a combination of a verb and a preposition, a verb and an adverb, or a verb with both an adverb and a preposition, any of which are part of the syntax of the sentence. Sentences may contain direct and indirect objects in addition to the phrasal verb. Phrasal verbs are particularly frequent in the English language. A phrasal verb often has a different meaning of the original verb. The purpose of study is to find and to analyze the data about the verb âgoâ with the particles (back to, on, and out) which are available in the novel based on semantic and syntactic analysis. The data are taken from the âNew Moonâ novel by Stephenie Meyer. In semantics analysis, the data of verb a âgoâ is analyzed both as singular verb and phrasal verb. In syntactic analysis, the data is analyzed and determined its function in phrase, clause, or sentence. When it is as phrasal verb and joins many particles, it will create new meaning and different meaning depends on the particles which are joined. When it is as phrasal verb, it has particular meaning, and it cannot be separated or omitted one another, since it will have different meaning if it is separated or omitted. The phrasal verb a âgoâ with its certain particle may have a different meaning; it depends on the context of the data; and after analyzing all data, the writer can conclude that the phrasal verb, when it is joined with its particles, it can be separable or non-separable.KEY WORDS: Verbs, phrasal verbs, âNew Moonâ novel, prepositions, particles, semantics, syntax, particles, and new meaning and different meaning.About the Author: Jauhar Helmie, M.Hum. is a Lecturer at the Department of English Education FKIP UNSUR (Faculty of Education and Teacher Training, Suryakancana University) in Cianjur, West Java, Indonesia. For academic purposes, the author can be contacted via e-mail at: jauhar_3rd@yahoo.co.idHow to cite this article? Helmie, Jauhar. (2015). âVerb Go (back to, on, and out) in English for TEFL in the Novel of New Moon by Stephenie Meyer: The Syntactic and Semantic Analysisâ in EDUCARE: International Journal for Educational Studies, Vol.7(2) February, pp.123-134. Bandung, Indonesia: Minda Masagi Press and UMP Purwokerto, ISSN 1979-7877. Chronicle of the article: Accepted (November 21, 2014); Revised (December 29, 2014); and Published (February 28, 2015).